2017
DOI: 10.1016/j.neuroimage.2017.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation in the posterior mid-cingulate cortex reflects perceptual transitions during binocular rivalry: Evidence from simultaneous EEG-fMRI

Abstract: Binocular rivalry is a phenomenon in which perception spontaneously shifts between two different images that are dichoptically presented to the viewer. By elucidating the cortical networks responsible for these stochastic fluctuations in perception, we can potentially learn much about the neural correlates of visual awareness. We obtained concurrent EEG-fMRI data for a group of 20 healthy human subjects during the continuous presentation of dichoptic visual stimuli. The two eyes’ images were tagged with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…locus coeruleus 61 which is the source of noradrenaline in the forebrain 62 and is involved in attention, or raphe nuclei, responsible for the release of serotonin 63 , whose levels have been shown to affect rivalry alternations 64 ) that projects to these frontal structures. While medial frontal activation has been reported in a few fMRI studies of bistable perception 15 , 20 , 21 , 23 , 24 , most of these studies found activations in lateral prefrontal regions. The region that is most consistently implicated in imaging studies (also after controlling for the matched duration 16 and no-report criticism 19 , 65 , 66 ) is the inferior frontal cortex (IFC).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…locus coeruleus 61 which is the source of noradrenaline in the forebrain 62 and is involved in attention, or raphe nuclei, responsible for the release of serotonin 63 , whose levels have been shown to affect rivalry alternations 64 ) that projects to these frontal structures. While medial frontal activation has been reported in a few fMRI studies of bistable perception 15 , 20 , 21 , 23 , 24 , most of these studies found activations in lateral prefrontal regions. The region that is most consistently implicated in imaging studies (also after controlling for the matched duration 16 and no-report criticism 19 , 65 , 66 ) is the inferior frontal cortex (IFC).…”
Section: Discussionmentioning
confidence: 95%
“…These neurons did not show selective responses during the non-rivalrous condition. Inspired by fMRI reports of frontal involvement in perceptual transitions 15 , 16 , 21 , 23 , 24 , 40 42 (but see ref. 43 ) we looked for units that changed their FR compared to baseline around the perceptual transitions, irrespective of image identity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During binocular rivalry, dissimilar monocular images presented to each eye compete for perceptual dominance, with conscious awareness typically fluctuating spontaneously between each image (Alais, 2012;Alais & Blake, 2005;Levelt, 1965;Maier, Panagiotaropoulos, Tsuchiya, & Keliris, 2012). When two flickering stimuli compete during rivalry, the relative strength of frequency-tagged activity positively correlates with behavioural reports of the dominant image (Bock, Fesi, Baillet, & Mendola, 2019;Brown & Norcia, 1997;Cosmelli et al, 2004;Jamison, Roy, He, Engel, & He, 2015;Kamphuisen, Bauer, & van Ee, 2008;Katyal et al, 2016;Lansing, 1964;Lawwill & Biersdorf, 1968;Roy, Jamison, He, Engel, & He, 2017;Srinivasan, Russell, Edelman, & Tononi, 1999;Sutoyo & Srinivasan, 2009;Tononi et al, 1998;Zhang et al, 2011) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when stimuli are flickered to generate a steady-state visual evoked potential (SSVEP), the signatures of competition can be found in the occipital and middle temporal (hMT/V5) visual areas (Zhang, Jamison, Engel, He, & He, 2011 ). Investigations of concurrent SSVEP and fMRI studies suggest involvement of other brain areas in parietal and cingulate regions alongside early visual areas (Roy, Jamison, He, Engel, & He, 2017 ). Thus, early visual areas show competitive interactions with coordinated activity occurring throughout the visual system as a consequence of resolving rivalry.…”
Section: Introductionmentioning
confidence: 99%